2022
DOI: 10.1155/2022/4806163
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Intestinal Flora Balance Therapy Based on Probiotic Support Improves Cognitive Function and Symptoms in Patients with Alzheimer’s Disease: A Systematic Review and Meta‐analysis

Abstract: Objective. The clinical value of intestinal flora balance therapy based on probiotic support in improving cognitive function and symptoms of patients with Alzheimer’s disease was to systematically evaluate, so as to provide evidence-based medicine basis for the promotion and use of this therapy. Methods. The randomized controlled trials (RCTs) were searched for the improvement of cognitive function and symptoms of patients with Alzheimer’s disease by intestinal flora balance therapy supported mainly by probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Therefore, in addition to correcting the altered microbiota with probiotics and prebiotics, it is necessary to correct the deficit of the nutrients that interact with the microbiota. Correction of altered gut microbiota using probiotics may improve cognitive function and instant memory in patients with AD ( Agahi et al, 2018 ; Tamtaji et al, 2019 ; Akbari et al, 2020 ; Doulberis et al, 2021 ; González Cordero et al, 2022 ; Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to correcting the altered microbiota with probiotics and prebiotics, it is necessary to correct the deficit of the nutrients that interact with the microbiota. Correction of altered gut microbiota using probiotics may improve cognitive function and instant memory in patients with AD ( Agahi et al, 2018 ; Tamtaji et al, 2019 ; Akbari et al, 2020 ; Doulberis et al, 2021 ; González Cordero et al, 2022 ; Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is one of the limitations of the study of AD, since the psychological and cognitive state is often not related to the physical and biochemical state of the brain. This is one of the reasons for the difficulty in conducting RCT with good methodological quality to study the relationship between nutrition and AD ( Liu et al, 2022 ). Nutritional interventions are good non-pharmacological tools for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the association between nonfood pre-or probiotic use and cognitive function has been inconsistent. Several meta-analyses have shown that probiotic treatment improves cognitive impairment [21][22][23][24]. However, some studies do not support the positive effects of probiotics, prebiotics, and fermented foods on cognitive function in elder populations [12,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Given that pharmacology and nutrition have some points in common, we will also discuss some data we have found regarding the relationship between nutrition and AD. Various nutrients and nutraceuticals have been linked to improvements in cognition and other psychological aspects related to AD ( Guzman-Martinez et al, 2021 ; Abduljawad et al, 2022 ; Mahnashi et al, 2022 ; Xu Lou et al, 2023 ) Some examples include Gingko Biloba ( Liao et al, 2020 ), Melissa Officinalis ( Noguchi-Shinohara et al, 2020 ; Noguchi-Shinohara et al, 2022 ), Ginseng ( Ahmad et al, 2023 ), anti-inflammatory fatty acids ( Albrahim, 2020 ), medium-chain fatty acids ( Juby et al, 2022 ), ketone bodies ( Avgerinos et al, 2020a ), saffron ( Avgerinos et al, 2020b ; Talebi et al, 2021 ), fenugreek seed ( Foroumandi et al, 2023 ), genistein ( Viña et al, 2022 ), sodium oligomannate ( Xiao et al, 2021 ), anthocyanin ( Suresh et al, 2022 ), microbiota and probiotics ( Den et al, 2020 ; Maitre et al, 2021 ; Liu et al, 2022 ; Naomi et al, 2022 ), benfotiamine ( Gibson et al, 2020 ), omega-3 fatty acids ( Canhada et al, 2018 ; Jernerén et al, 2019 ), resveratrol ( Gu et al, 2021 ; Buglio et al, 2022 ; Fang et al, 2022 ; Tosatti et al, 2022 ), melatonin ( Tseng et al, 2022 ), citicoline ( Bonvicini et al, 2023 ), folic acid, vitamin B12 ( Chen et al, 2021 ), vitamins and minerals ( Mccleery et al, 2018 ; Karthika et al, 2022 ), selenium ( Pereira et al, 2022 ), vitamin D ( Jia et al, 2019 ), and mangosteen ( Muangpaisan et al, 2022 ). However, some studies do not support the efficacy of certain nutrients ( Zhu et al, 2018 ; Thancharoen et al, 2019 ; Araya-Quintanilla et al, 2020 ; Burckhardt et al, 2020 ; Du et al, 2020 ; Prabhakar et al, 2020 ; Shim et al, 2021 ; Tofiq et al, 2021 ; Takada et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%